Effect of surface treatment on shear bond strength of artificial teeth to the denture base (Mustansiria Dental Journal, 2018)
Fracture or debonding of plastic teeth from the denture base are common clinicalproblems, the optimal combination of acrylic resin denture teeth and microware cureddenture base resin is not well known .one hundred and twenty teeth (florident, acrylicteeth cross-linked, china) were prepared and cured by heat cured (AkrilEks, heatcuringresin for denture powder liquid, GuLSA LTD. Izmir-Turkey), and microwarecured (Acron mc, microwave-curing denture base resin powder liquid, GCLABTechnologies inc. Alsip,IL60803 Japan) acrylic resin were used, then the teeth weredivided into six groups and treated with different surface treatment, the first groupreceived no further treatment(control); the second group treatment with diatoricpreparation; the third group treated with thinner(Turpentine-DYNA CoAT, Thinner,Netherlands); the fourth group treated with tone(Propanone, Acetone, England 99%Purity-Analyer); the fifth group were diatoric conditioned with acetone; the sixthgroup were diatoric conditioned with thinner;(2nd group, 5th group and 6th group hadbeen a cutting mesiodistal retention grooves 2mm deep and 3mm wide acute intoridge lap in acrylic resin teeth. One hundred and twenty specimens were divided intotwo groups, first one was processed by conventional method and the other oneprocessed by microwave method and then tested by instron universal testing machine(instron corporation 1195,canton mass).The results showed than microwave-curedresin has a significant lower shear bond strength(SBS) mean values than water bathcuredresin to all denture teeth types. All surface treatment application improvedthe(SBS) significantly level at(p value < 0.05), while the sixth group (diatoricconditioned with thinner) showed the highest(SBS) than other group. The types ofacrylic denture resin, surface treatment and curing technique influenced the shearbond strength of the tooth to the base the results of this study influenced the shearbond strength of the tooth to the base. The results of this study indicate that diatoriccondition with thinner may be recommended to be applied on the denture ridge lapprior to denture base processing.